2021
DOI: 10.1111/ans.17168
|View full text |Cite
|
Sign up to set email alerts
|

“The odds were stacked against me”: a qualitative study of underrepresented minorities in surgical training

Abstract: Background The Royal Australasian College of Surgeons (RACS) is expected to provide surgical care to a diverse patient population across Australia and New Zealand (ANZ). To improve the quality‐of‐care individuals receive, the surgical workforce must reflect the population it serves. Achieving diversity within RACS will strengthen therapeutic relationships with patients and promote an inclusive culture. This study investigates the perspectives of underrepresented minority (URM) trainees to highlight barriers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
1
14
1
Order By: Relevance
“…Thirteen articles indicted race as the basis for discriminatory practices in supervision. Yuce et al (2020), Constantine and Sue (2007), Davis (2017), Hu et al (2019), Kleintjes and Swartz (1996), Kristoffersson et al (2021), Nguemeni Tiako et al (2021), Nilsson and Duan (2007), Senreich and Dale (2021), Thackwell et al (2016), and McKenzie-Mavinga and George (2020) discussed the racial disparities that exist within the supervisory relationship. Most indicated experiencing everyday racism and different standards on evaluations than their White counterparts (Yuce et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen articles indicted race as the basis for discriminatory practices in supervision. Yuce et al (2020), Constantine and Sue (2007), Davis (2017), Hu et al (2019), Kleintjes and Swartz (1996), Kristoffersson et al (2021), Nguemeni Tiako et al (2021), Nilsson and Duan (2007), Senreich and Dale (2021), Thackwell et al (2016), and McKenzie-Mavinga and George (2020) discussed the racial disparities that exist within the supervisory relationship. Most indicated experiencing everyday racism and different standards on evaluations than their White counterparts (Yuce et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Yuce et al (2020), Constantine and Sue (2007), Davis (2017), Hu et al (2019), Kleintjes and Swartz (1996), Kristoffersson et al (2021), Nguemeni Tiako et al (2021), Nilsson and Duan (2007), Senreich and Dale (2021), Thackwell et al (2016), and McKenzie-Mavinga and George (2020) discussed the racial disparities that exist within the supervisory relationship. Most indicated experiencing everyday racism and different standards on evaluations than their White counterparts (Yuce et al, 2020). Some studies reported participants experiencing stereotypical assumptions about their status within the organization (Constantine & Sue, 2007) and being mistaken for a “non-physician” (Yuce et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations